2019
DOI: 10.1590/01047760201925032647
|View full text |Cite
|
Sign up to set email alerts
|

MINI-CUTTING TECHNIQUE FOR VEGETATIVE PROPAGATION OF Paratecoma peroba

Abstract: Rooting percentage was positively related to lower substrate density. More vigorous root system was obtained with leaf area maintenance. The apical mini-cutting of 10 cm is more adequate in the production of clones. The protocol will enable mass propagation and recovering the P. peroba population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
8
0
5
Order By: Relevance
“…High percentage of bamboo explants emitting shoots (up to 97%) had already been observed by other researchers (GARCÍA-RAMÍREZ et al, 2007;SINGH et al, 2012b;PANDEY;SINGH, 2012;SINGH et al, 2012a;HOULLOU;DE SOUZA, 2016a). In these cases, the better results may be associated with inherent characteristics of the matrix plant (SANDHU; WANI; JIMÉNEZ, 2018;ARAÚJO et al, 2019).…”
Section: Experiments 2 -Ex Vitro Rooting and Acclimatizationmentioning
confidence: 53%
“…High percentage of bamboo explants emitting shoots (up to 97%) had already been observed by other researchers (GARCÍA-RAMÍREZ et al, 2007;SINGH et al, 2012b;PANDEY;SINGH, 2012;SINGH et al, 2012a;HOULLOU;DE SOUZA, 2016a). In these cases, the better results may be associated with inherent characteristics of the matrix plant (SANDHU; WANI; JIMÉNEZ, 2018;ARAÚJO et al, 2019).…”
Section: Experiments 2 -Ex Vitro Rooting and Acclimatizationmentioning
confidence: 53%
“…However, Rodrigues (2018) used mini-cuttings of P. reticulata with 15 cm in length and observed lower percentages of propagule survival (13.33% for apical mini-cuttings, 18.33% for intermediate, and 16.67% for basal, N = 60). Araújo et al (2019), working with Paratecoma peroba mini-cuttings, found that 10 cm apical mini-cuttings showed the greatest survival (90%) and rooting (80%) rates, compared to shorter mini-cuttings, 90 days after staking. However, in the seedling production of Azadirachta indica by mini-cutting, Fernandes et al (2017), using three sizes of mini-cuttings (5, 8, and 11 cm), observed that the size of the propagules did not affect rooting, although seedlings produced from mini-cuttings of greater length showed higher Dickson Quality Index (DQI) values.…”
Section: Experiments 2 -Mini-garden Management and Clonal Seedling Promentioning
confidence: 99%
“…The mini-cuttings were made with a size of 10 cm, in which the apical yolk and 100% of the leaf area were maintained (Araújo et al, 2019). After preparation, the minicuttings were disinfected by immersing, for 1 minute, in 0.5% sodium hypochlorite, then rinsing in running water, and then immersed in 0.2% fungicide.…”
Section: Formation Of the Mini-clonal Hedgementioning
confidence: 99%
“…Through DRIS indexes, it was possible to calculate the Nutritional balance index medium (NBIm), which is the sum of the DRIS indices in module, divided by the number of nutrients involved. The closer to zero the value of the NBIm, the lower the nutritional imbalance of the plants and, potentially, the higher production (Araújo et al, 2019;Malavolta et al, 1997).…”
Section: Evaluation Of Clonesmentioning
confidence: 99%